On the Meteoric Smoke Particle Detector SPID: Measurements and analysis from the G-chaser rocket campaign - Trollvik, Henriette Marie Tveitnes (UiT Norges arktiske universitet, 2019)
The Smoke Particle Impact Detector (SPID), newly designed at the University of Tromsø, was launched from Andøya 09:13 UTC the 13. January 2019. SPID is designed to detect meteoric smoke particles (MSPs) in winter mesospheric conditions. The rocket had a velocity of 1600 ms-1 at ~55 km where the nosecone was separated. At ~ 60km, SPID detected a signal of 17nA on the middle plate. The dynamics of the particles entering the detector was investigated taking into account the drag of the neutral airflow as well as the electric field generated by the bias voltages of the detector. These conditions were applied to a model of the size and charge of mesospheric dust in the range of radii 0.5 to 8 nm. For this model of the meteoric dust we find that 97 percent of particles that the rocket encounters would reach the middle plate and that 30 percent of the particles would hit the middle plate directly at 60 km. Estimations of dust densities that could explain the measured current vary between 10^10 and 101^3 per m^-3. The density of positive ions is close to that of MSPs, and so it is also possible that the measured current, or a fraction of it, is caused by ions. A secondary goal of the campaign was to investigate the relation between MSPs and the winter radar echoes called Polar Mesospheric Winter Echoes(PMWE). For this, the background atmospheric conditions were monitored with the radar systems MAARSY (53.5 MHz) and EISCAT (224 MHz). The EISCAT measured incoherent scatter which showed weak precipitation above 85 km. MAARSY did not observe PMWE activity during the launch, but on the days prior and after launch. Because it is a prerequisite to observe PMWE that the electron density is sufficiently high, we cannot draw any conclusions on the link between PMWE and MSP from the presented observations. The spectral analysis of the measured current shows strong rotational effects at higher altitudes. The Power spectrum follows the Kolmogorov slope of k^-5/3 into the Bragg scale of MAARSY, suggesting turbulent conditions ...